The Ideal Influencer: How Influencer Coaches and Platforms Construct Creators as Monetizing for the Right Reasons - Taylor Annabell (Social Media + Society)
This article examines the construction of the ideal influencer across two sites of articulation within the influencer ecology: influencer coaches and platforms. It seeks to make visible the normative model that underpins and regulates influencer identities, practices and monetization, which is tied to the interests and values of different actors. Drawing on a sample of 70 TikTok videos and Instagram posts from influencer coaches, a dataset of 69 TikTok and Instagram policies, and a walkthrough of TikTok and Instagram creator accounts, I analyze what constitutes the ideal influencer through a critical feminist approach to influencer labor. In content shared by influencer coaches, the influencer is framed as a strategic actor who offers value to their community and embraces their identity as a professional entrepreneur. Through platform policies and interface design, the influencer is constructed as a skilful creator who engages their audiences in the “right” ways and assumes responsibility for complying with regulations. I argue that these constructions converge on the assertion that influencers should monetize for the “right” reasons. This steers influencers toward a worker subjectivity that is ideal for the platform, linking the construction of influencers as users—rather than workers who should be rewarded but not compensated for their labor—to the professionalization of the industry.